Sistem Pendukung Keputusan Dalam Pemilihan E-Wallet Terbaik dengan Metode ROC dan MOORA - Ramadan, Bagus Satrio; Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In the digital era, the use of e-wallets is increasing along with the development of financial technology. However, the many choices of e-wallets available cause difficulties for users in making choices that suit their needs. This problem requires a solution in the form of a decision support system that can help users choose the best e-wallet. This research uses the Rank Order Centroid (ROC) method and Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) to solve these problems. The ROC method is used to determine the weight of the criteria used, while the MOORA method is applied to evaluate e-wallet alternatives based on criteria that have been weighted. The selection of the ROC method is based on its ability to provide more accurate weighting based on the preferences of decision makers, while MOORA was chosen for its efficiency in processing and comparing complex alternatives. This research aims to develop a system that can provide recommendations for the best e-wallet based on criteria such as ease of use, security, transaction fees, and additional features. The contribution of this research lies in the application of the combined ROC and MOORA methods in the context of e-wallet selection, which has not been widely explored before. The results showed that based on the information obtained from table 5, the MOORA and ROC methods produced a value for the Dana application of 1.103 as alternative C1. With this highest value, Dana application is chosen as the best e-wallet. Thus, the proposed decision support system successfully provides the best e-wallet recommendations with a high level of accuracy and is able to accommodate various user preferences